AIDS Ryan White CARE Act. (U.S. Congressional Research., 2004)
Summarizes the provisions of Ryan White Comprehensive AIDS Resources Emergency (CARE) Act programs, which provide assistance to cities and States for health care costs and support services for persons with HIV and AIDS. Discusses the services supported by each program, describes eligibility and distribution requirements, and lists Federal funding amounts.